Modern financial investment tools, future contracts as a model - Maram Al Boucherbi; Qasim Askari (Genius Journals, 2022)
Futures contracts are among the modern contracts that are widely traded in the global financial markets. They are the most important contemporary intellectual products in the field of financial management. The main objective of futures contracts is to reduce risks due to changes in prices according to supply and demand factors and to achieve capital gains through speculation in the prices of these contracts. Futures contracts are standard contracts in the sense that they are all subject to specific provisions set by the organized market, and the organized market is the guarantor of their implementation, through settlement houses that meet the seller and buyer a specific financial margin, which is followed up and down until the term of the contract.
Keywords: investment tools; future contracts